Multidecadal vegetation transformations of a New Mexico ponderosa pine landscape after severe fires and aerial seeding - Wion, Andreas P.; Stevens, Jens T.; Beeley, Kay; Oertel, Rebecca; Margolis, Ellis Q.; Allen, Craig D. (Ecological applications, 2024)
Wildfires and climate change increasingly are transforming vegetation composition and structure, and postfire management may have long‐lasting effects on ecosystem reorganization. Postfire aerial seeding treatments are commonly used to reduce runoff and soil erosion, but little is known about how seeding treatments affect native vegetation recovery over long periods of time, particularly in type‐converted forests that have been dramatically transformed by the effects of repeated, high‐severity fire. In this study, we analyze and report on a rare long‐term (23‐year) dataset that documents vegetation dynamics following a 1996 post‐fire aerial seeding treatment and a subsequent 2011 high‐severity reburn in a dry conifer landscape of northern New Mexico, USA. Repeated surveys between 1997 and 2019 of 49 permanent transects were analyzed for differences in vegetation cover, richness, and diversity between seeded and unseeded areas, and to characterize the development of seeded and unseeded vegetation communities through time and across gradients of burn severity, elevation, and soil‐available water capacity. Seeded plots showed no significant difference in bare ground cover during the initial years postfire relative to unseeded plots. Postfire seeding led to a clear and sustained divergence in herbaceous community composition. Seeded plots had a much higher cover of non‐native graminoids, primarily Bromus inermis, a likely contaminant in the seed mix. High‐severity reburning of all plots in 2011 reduced native graminoid cover by half at seeded plots compared with both prefire levels and with plots that were unseeded following the initial 1996 fire. In addition, higher fire severity was associated with increased non‐native graminoid cover and reduced native graminoid cover. This study documents fire‐driven ecosystem transformation from conifer forest into a shrub‐and‐grass‐dominated system, reinforced by aerial seeding of grasses and high‐severity reburning. This unique long‐term dataset illustrates that post‐fire seeding carries significant risks of unwanted non‐native species invasions that persist through subsequent fires—thus alternative postfire management actions merit consideration to better support native ecosystem resilience given emergent climate change and increasing disturbance. This study also highlights the importance of long‐term monitoring of postfire vegetation dynamics, as short‐term assessments miss key elements of complex ecosystem responses to fire and postfire management actions.